Macro-fiscal volatility and the composition of public spending - Sara Maria Riscado; Juraj Stanécík; Timo Välilä (European Investment Bank (EIB), 2010)
Earlier empirical literature has examined some long- and medium-term aspects of macro-fiscal volatility while leaving its short-term fiscal impact unexplored. To help fill that gap, we examine the impact of macro-fiscal volatility on the composition of public spending. To that end, we analyse a panel of 10 EU countries during 1991-2007. Our results suggest that contemporaneous increases in the volatility of regularly collected revenues such as the VAT and income taxes tend to tilt the expenditure composition in favour of public investment. In contrast, increases in the volatility of ad hoc-type of taxes such as capital taxes tend to favour public consumption spending. A possible explanation to these differences concerns news about the underlying economic conditions embedded in short-term volatility changes: the policy maker may be more inclined to increase public investment in response to persistent changes in the economic conditions, while temporary changes may prompt a reaction on consumption spending.
Keywords: H29; H50; E62; E32; C33; 330; tax volatility; public investment; public consumption